How Teacher's Beliefs Are Reflected On What They Do In Their Classes: A Report On An English Classroom Observation - Solís Hernández, Mayra (2021)
This article presents the findings of a classroom observation done to determine if a teacher's beliefs about the method used, control, and student initiative are reflected on her behavior in an English class at the university level.